Glecaprevir/Pibrentasvir Treatment in Liver or Kidney Transplant Patients With Hepatitis C Virus Infection. Issue 4 (25th July 2018) - Reau, Nancy; Kwo, Paul Y.; Rhee, Susan; Brown, Robert S.; Agarwal, Kosh; Angus, Peter; Gane, Edward; Kao, Jia‐Horng; Mantry, Parvez S.; Mutimer, David; Reddy, K. Rajender; Tran, Tram T.; et al.
Abstract : Well‐tolerated, ribavirin‐free, pangenotypic hepatitis C virus (HCV) treatments for transplant recipients remain a high priority. Once‐daily glecaprevir/pibrentasvir demonstrates high rates of sustained virologic response at 12 weeks posttreatment (SVR12) across all major HCV genotypes (GTs). This trial evaluated the safety and efficacy of glecaprevir/pibrentasvir for patients with chronic HCV GT1‐6 infection who had received a liver or kidney transplant. MAGELLAN‐2 was a phase 3, open‐label trial conducted in patients who were ≥3 months posttransplant. Patients without cirrhosis who were HCV treatment‐naive (GT1‐6) or treatment‐experienced (GT1, 2, 4‐6; with interferon‐based therapy with or without sofosbuvir, or sofosbuvir plus ribavirin) received glecaprevir/pibrentasvir (300/120 mg) once daily for 12 weeks. The primary endpoint compared the percentage of patients receiving glecaprevir/pibrentasvir with SVR12 to a historic SVR12 rate based on the standard of care. Safety of glecaprevir/pibrentasvir was assessed. In total, 80 liver transplant and 20 kidney transplant patients participated in the trial. Most patients had no or minimal fibrosis (80% had fibrosis scores F0‐F1) and were infected with HCV GT1 (57%) or GT3 (24%). The overall SVR12 was 98% (n/N = 98/100; 95% confidence interval, 95.3%–100%), which exceeded the prespecified historic standard‐of‐care SVR12 threshold of 94%. One patient experienced virologic failure. One patient discontinued because of an adverse event considered to be unrelated to treatment; this patient achieved SVR12. Adverse events were mostly mild in severity, and laboratory abnormalities were infrequent. Conclusion: Once‐daily glecaprevir/pibrentasvir for 12 weeks is a well‐tolerated and efficacious, ribavirin‐free treatment for patients with chronic HCV GT1‐6 infection who have received a liver or kidney transplant. (ClinicalTrials.gov NCT02692703.) (Hepatology 2018; 00:000‐000).